CHALLENGES AND SOLLUTION IN THE SUPPLY CHAIN OF INDIAN VEGETABLE MARKET: A REVIEW - Bharati Pujari (International Journal of Research Science and Management, 2016)
India’s population is very high. More than 120 crore people live in India. For that reason demand for vegetables is very high also. India is the second largest producer of vegetables in the world. But due to lack of proper supply chain management a lot of wastage is happening. As vegetables belong to perishable goods, within a short span of time these items will have no use. To reduce the wastage these items require proper storage, packaging, handling and transportation. The main objective of the study is to find out the issues and challenges in the supply chain of vegetables and to find out the solution for the problem in supply chain. The present study undertakes a thorough review of basic and contemporary literature available. The study is based on secondary sources. The information has been collected from various published sources like journals, newspaper, articles, magazines etc and tries to explain the barriers in the supply chain of vegetables. The study found that unavailability of cold chain, poor infrastructural facilities, high cost, wastage of fresh produce are the barriers which are affecting the vegetable sector. The problem of supply chain will be solved by development of cold chain infrastructure, proper connectivity, using modern technology, suitable packaging, awareness and knowledge level of farmers etc. In an agrarian economy like India vegetable plays a very important role. So supply chain of vegetable plays a significant role in developing the food sector.